The Effect of inulin addition on the sensory attributes of pearl-millet based dairy beverage (Rab) - Zahara Ali Shams, Nikita Wadhawan, Karun Chandalia (Indian Journal of Dairy Science, 2024)
Being a traditional part of Rajasthani cuisine, Rab is widely consumed and relished for its taste. Inulin (prebiotic) has been proven beneficial for gut health. The addition of inulin in Rab results in a superfood; containing characteristics of traditional as well as functional beverages. The investigation was performed to prepare and standardize pearl millet (PM) and horse gram dal (HGD) Rab with the inulin. The inulin was added at 0%, 1%, 3%, and 5% rates and let ferment for 6-7h, at 350C. All the fermented treatments were stored at 40C. All treatments were evaluated for sensory characteristics. All treatments were tested for sensory characteristics including color, consistency, taste and flavor, mouthfeel, aftertaste, and overall acceptability on the Nine-point Hedonic scale and obtained scores above 7 points. It was concluded that the inclusion of inulin significantly improved the sensory characteristics of the functional beverage.